2008
DOI: 10.1093/aob/mcn121
|View full text |Cite
|
Sign up to set email alerts
|

Rice germination and seedling growth in the absence of oxygen

Abstract: Although there is still much to learn about the biochemical and molecular basis of anaerobic rice germination, the ability of rice to maintain an active fermentative metabolism (i.e. by fuelling the glycolytic pathway with readily fermentable carbohydrates) is certainly crucial. The results obtained through microarray-based transcript profiling confirm most of the previous evidence based on single-gene studies and biochemical analysis, and highlight new aspects of the molecular response of the rice coleoptile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
239
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 261 publications
(251 citation statements)
references
References 147 publications
10
239
1
1
Order By: Relevance
“…3B). Notably, such an increase in carbon flux through glycolysis and a sharp decline in coleoptile growth have already been reported (Mohanty et al, 1993;Gibbs et al, 2000;Magneschi and Perata, 2009), highlighting the importance of ethanolic fermentation in combination with glycolysis for energy production under anaerobiosis. On the other hand, aerobic glycolysis showed that significant amounts of pyruvate were utilized in the oxidative conversion to acetyl-CoA, thus enabling its entry into the TCA cycle for energy production (Fig.…”
Section: Glycolysismentioning
confidence: 73%
See 2 more Smart Citations
“…3B). Notably, such an increase in carbon flux through glycolysis and a sharp decline in coleoptile growth have already been reported (Mohanty et al, 1993;Gibbs et al, 2000;Magneschi and Perata, 2009), highlighting the importance of ethanolic fermentation in combination with glycolysis for energy production under anaerobiosis. On the other hand, aerobic glycolysis showed that significant amounts of pyruvate were utilized in the oxidative conversion to acetyl-CoA, thus enabling its entry into the TCA cycle for energy production (Fig.…”
Section: Glycolysismentioning
confidence: 73%
“…In this regard, our simulation results suggested that the PPi could be produced toward the gluconeogenesis direction via reactions catalyzed by either PFP or pyruvate orthophosphate dikinase (PPDK), forming a substrate cycle in glycolysis. Such combined utilization of SUS, NDPK, UGPP, and PFP/PPDK for the breakdown of Suc is energetically more efficient than invertase, since they consume 1 mol of ATP less for each mol of Suc degraded (Guglielminetti et al, 1995;Magneschi and Perata, 2009). …”
Section: Suc Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, under conditions where oxygen is limited, an increase in glycolytic flux, modified Suc degradation, and a decrease in processes such as transport and various biosynthetic pathways occur. More specifically, a switch to the pyrophosphate (PPi)-linked enzymes, such as PPi-dependent phosphofructokinase and pyruvate orthophosphate dikinase, as well as the breakdown of Suc via Suc synthase conserves ATP, a response reported in a variety of studies Magneschi and Perata, 2009). …”
mentioning
confidence: 99%
“…Despite differences in tolerance to anaerobic conditions, plant size, and life cycle, the use of transcriptomic approaches to study the response to anaerobic conditions in Arabidopsis (Arabidopsis thaliana; Liu et al, 2005;Loreti et al, 2005;Van Dongen et al, 2009), rice (Oryza sativa; Lasanthi- Kudahettige et al, 2007;Magneschi and Perata, 2009), and poplar (Populus 3 canescens; Kreuzwieser et al, 2009) reveals similar changes in primary carbon metabolism. However, more global analysis of these studies also reveals that the number of genes that displayed significant changes in abundance varied greatly between species; in Arabidopsis, only 1,266 transcripts were altered in abundance in response to anoxia (Klok et al, 2002;Liu et al, 2005), 3,134 probe sets were observed to change sig-nificantly in rice coleoptiles under the conditions analyzed (Lasanthi-Kudahettige et al, 2007), while as many as 5,000 transcripts were altered in roots of poplar (Kreuzwieser et al, 2009).…”
mentioning
confidence: 99%